Stasanor of Soloi and the Government of Bactria during the Wars of the Diadochi - Mendoza Sanahuja, Marc (Anabasis. Studia Classica et Orientalia, 2017)
Stasanor of Soloi was a seasoned Greek Companion of Alexander III and the first satrap of Bactria-Sogdiana who achieved a certain political stability in his office. Even though his career is only known through some scanty passages in the sources, this paper tries to fill in the gaps and to reconstruct the government of this man over one of the key satrapies in the East. His policies towards the population of his territory - both local inhabitants and new settlers - and his relationship with other potentates bestowed him a solid post in one of the most tumultous periods of the Hellenistic history.